The Impact of FDI on Innovation in Target Firms - Joel Stiebale; Frank Reize (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper contributes to the ongoing debate on the welfare effects of foreign direct investment by investigating the effects of cross-border mergers and acquisitions on innovation activities in target firms. The empirical analysis is based on survey and ownership data for a large sample of small- and medium- sized German firms. After controlling for endogeneity and selection bias, it is found that foreign takeovers have a large negative impact on the propensity to perform innovation activities and a negative impact on average R&D expenditures in innovative firms. Furthermore, innovation output, measured as the share of sales from product innovations is not significantly affected by a foreign takeover for a given amount of innovation efforts. Hence, the estimation results do not show any evidence of significant technology spillovers through foreign direct investment in form of a higher innovation success.
Keywords: D21; F23; G34; C31; O31; O33; 330; Multinational enterprises; mergers and acquisitions; innovation; Direktinvestition; Ausländisch; Technologietransfer; Innovation; Industrielle Forschung; Klein- und Mittelunternehmen; Übernahme; Fusion; Multinationales Unternehmen; Deutschland